A Path Towards Wholeness: Identifying the Experiences of Clinicians Who Practice Psychotherapy and Nichiren Buddhism - Shirai, Seiko (Auckland University of Technology, 2017)
This research studies the experiences of clinicians who practice Psychotherapy and Nichiren Buddhism. Five people were selected from four countries, New Zealand, England, America and Japan. The study seeks to understand some aspects of where both practices overlap and what they say about transforming human suffering. The study utilised the hermeneutic phenomenology. This methodology is underpinned by philosophies which are the most suitable for exploring and interpreting the clinicians’ lived experiences. The study has revealed three central themes: Compassion for oneself – being true to oneself, a determined effort to help others, and a wholehearted commitment to life. These themes describe an inner transformation of the self as the starting point of transformation in the environment. The study discusses the participants’ process of engaging with inner conflict and cultivating compassion. The participants’ experiences suggest that our vulnerabilities are not seen as an obstacle against compassion, but rather as a catalyst that makes the emergence of compassion possible. The study explores how our individual inner transformation can make a positive impact on our immediate environment and society.
Keywords: Wholeness; Mindfulness; Nichiren Buddhism; Self-compassion; Courage; Faith; Personal transformation